2017
DOI: 10.1055/s-0042-117723
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hematological and Inflammatory Responses to High-intensity Exercise Tests: Impact of Duration and Mode of Exercise

Abstract: The purpose of this study was to investigate the hematological and inflammatory responses to 4 maximal high-intensity protocols, considering energy expenditure in each test. 9 healthy volunteers performed 4 high-intensity exercise tests of short [Wingate (WANT); Repeated-sprints (RSA)] and long durations [Continuous VO test (VCONT); intermittent VO test (VINT)] in a cycle-ergometer, until exhaustion. Hematological parameters and IL-6, IL-10 and creatine kinase (CK) levels were determined before (PRE), POST, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…According to the inflammatory cytokine analysis, inflammation in the testis was significantly enhanced in the IE group compared to the control group. This reinforces previous results that high-intensity exercise can cause inflammation [25]. Moreover, several studies have shown that systemic inflammation can inhibit testosterone secretion without relying on hypothalamic-pituitary levels, and also cause damage to the sperm [26, 27].…”
Section: Discussionsupporting
confidence: 89%
“…According to the inflammatory cytokine analysis, inflammation in the testis was significantly enhanced in the IE group compared to the control group. This reinforces previous results that high-intensity exercise can cause inflammation [25]. Moreover, several studies have shown that systemic inflammation can inhibit testosterone secretion without relying on hypothalamic-pituitary levels, and also cause damage to the sperm [26, 27].…”
Section: Discussionsupporting
confidence: 89%
“…Other studies found increased levels of specific blood cytokines during intense physical exercise. For instance, after long-duration and high intensity exercise, the circulating levels of IL-6 can increase by up to 100-fold [21], producing a strong anti-inflammatory response [22]. In this respect, although IL-6 is classified as an inflammatory cytokine, in physical exercise it is considered an anti-inflammatory cytokine that regulates the acute inflammatory response [5].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the use of IL-6 and IL-10 in the treatment of circulatory diseases, IL-6 has been shown to increase the secretion of cortisol and IL-10. These data indicate that both hormones and cytokines contribute to the anti-inflammatory effects of exercise [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…This biphasic response is consistent with studies using strenuous or interval exercise. 6 , 9 , 55 , 56 , 57 , 58 The delayed exercise-induced lymphocytopenia may occur for several hours 5 , 6 , 55 and reflects the preferential movement of lymphocyte subtypes with potent effector functions (e.g., NK cells, γδ T cells, and CD8 + T cells) out of the blood 11 as an integral part of the physiological stress response to exercise. 11 Reduced lymphocyte count and function is associated with immunosuppression and increased risk for infection, 12 although this remains a controversial topic.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Some previous studies have shown that an acute session of SIT or HIIE induces large alterations on hematologic profile, redox status and metabolic indices. 5 , 6 , 7 , 8 However, few studies have attempted to compare the effects of different HIIE protocols on these responses, 6 , 7 while there is little or no information for HIIE performed at an intensity around VO 2 max and bout durations less than 1 min. 9 , 10 It is known that strenuous exercise may cause a temporary decrease in immune cell function, creating a potential “open window” for infection.…”
Section: Introductionmentioning
confidence: 99%